CitrusVol Validation for the Adjustment of Spray Volume in Treatments against Tetranychus urticae in Clementines - Fonte, Alberto; Garcerá, Cruz; Tena, Alejandro (MDPI, 2020)
The optimization of the water volume used to apply pesticides with airblast sprayers is key to reducing water footprint, costs, operational time and drift of pesticides. This study evaluated a new tool (CitrusVol) that adjusts the spray volume to the characteristics of the vegetation and the pesticide used to control the two-spotted spider mite Tetranychus urticae in clementine trees. This mite is one of the main citrus pests because it damages fruit before harvest. For this aim, a total of 20 applications against T. urticae were evaluated during two consecutive years in seven commercial orchards. In these orchards, we evaluated: (i) the distribution of the spray in tree canopies, (ii) pest density before and after the treatment, and (iii) fruit damage at harvest when conventional volumes and volumes adjusted with CitrusVol were applied. On average, CitrusVol reduced 36% the water volume used to control T. urticae in the 20 applications. This reduction in the spray volume involved a decrease in the coverage in some parts of the canopy. However, T. urticae density and fruit damage at harvest were similar in trees treated with the adjusted volume calculated with CitrusVol and the volume used by the owners of the orchard. Therefore, the spray volume recommended by CitrusVol is adequate to control T. urticae in clementines.